Staying in the Threshold. Bodies and Art in the Thought of Merleau-Ponty and Deleuze - Bandi, Fabrizia (Scenari, 2021)
In Merleau-Ponty and Deleuze’s philosophy, bodies and art are intrinsically intertwined. For both, these terms are connected to an ontological dimension, which is achievable just through a radical reconsideration of the subjectivity. The two philosophers analyze the condition of the body in relation to the artistic phenomenon (Merleau-Ponty via Cézanne and Deleuze via Bacon), reaching two different conditions of bodies, with different functions, but joined by the desire of exceeding. Moreover, these two perspectives are similar because, in both cases, art is able to lead us to focus on the threshold as a territory where the sensible is overstepped and kept at the same time.